ANALISIS PENGARUH INVESTMENT OPPORTUNITY SET (IOS) DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS BURSA EFEK INDONESIA PERIODE 2019-2021 - Mudawanah, Siti (Universitas La Tansa Mashiro, 2023)
The aim of this research is to analyze the influence of the Investment Opportunity Set (IOS) and dividend policy on company value in the BEI Consumer Non-Cyclicals sector during the 2019-2021 period. The Consumer Non-Cyclicals sector on the Indonesia Stock Exchange (BEI) has an important role in national economic stability, offering products and services needed by society in various economic conditions. The research method used is a quantitative method using secondary data. The population of this study was 98 companies in the Consumer Non-Cyclicals Sector of the Indonesian Stock Exchange for the 2019-2021 period, using a sample selection technique, namely purposive sampling, so that 14 companies were obtained as samples in this study. The data analysis technique uses multiple linear regression analysis with data processing using the SPSS V.20 application. The results and conclusions show that the Investment Opportunity Set (IOS) has an effect on the value of the Company, while dividend policy has no effect on the value of the Company, and together the Investment Opportunity Set (IOS) and dividend policy have an effect on the value of the Company.